MECHANISMS OF GRADONYMIC RELATIONS IN PHRASEOLOGICAL UNITS: A TYPOLOGICAL ANALYSIS OF ENGLISH AND UZBEK (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Gradonymy, the semantical relationship formed as a result of degree scale differentiation, has been a popular area of research within lexicology but has not been sufficiently studied at the level of phraseology. This paper will analyse the mechanisms used to express gradonymic relationships in English and Uzbek through phraseological units (PUs) in both languages. A comparative typological analysis and semiotic and context-based parameters will be used to review the five primary mechanisms used to express gradonymy: 1) scalar lexical substitution; 2) metaphor as a form of intensification; 3) syntactical amplification; 4) evaluative scaling; and 5) culturally established conceptual gradation.The results indicate that while both languages share the same universal cognitive basis for the conceptualisation of scalar concepts, they differ in the form of expression. English primarily relies on analytically based forms of intensification and metaphor; however, in contrast, the Uzbek language tends to rely heavily on repetition, expressive constructions, and culturally determined metaphoric/classificational intensification. All results from this paper have implications for phraseological semantics, theories of gradation, and typology across languages.